PRESERVATION OF UNIVERSITY LIBRARY FUND: SOCIAL ASPECT - Salkova, Larisa V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
This article deals with problem of library funds preservation through the example of Fundamental library of Tambov State University named after G. R. Derzhavina.